(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Pain, functional impairment, and decreased productivity are symptoms of work-related musculoskeletal diseases (WMSDs), which affect both those with physically demanding jobs and those with more sedentary work situations. Adjustments to the workstation, exercises to strengthen the muscles, and education on proper posture are all examples of ergonomic physiotherapy treatments. These therapies aim to reduce the incidence of these disorders by treating the underlying environmental and physiological reasons. This systematic review was conducted with the intention of determining whether or not ergonomic treatments (PEIs) administered by physiotherapists are effective in the prevention or management of work-related stress injuries (WMSDs). Between the years 2009 and 2025, the experiments were conducted using a randomization method. Six high-quality studies have shown that PEIs increase both functional outcomes and pain in the muscles and joints. PEIs also improve the results of functional tests. In particular, this is the case when the PEIs combine specialized strengthening exercises with modifications to the workstation. Due to limitations such as small sample sizes, the lack of participant blinding, and variation in intervention regimens, it is evident that more study of a high quality is required despite the fact that these potentially positive effects have been achieved.